No need to choose between innovation and internationalization: when pursuing two strategies at a time leads to firm superior performance - Nosi, Costanza; Pucci, Tommaso; Zanni, Lorenzo (Piccola Impresa / Small Business, 2017)
Whereas commonly innovation and internationalization have been studied disjointedly, many academics have recently questioned the relationship that there might be between these two strategic choices. The present study aims to determine whether businesses can concurrently attain internationalization and innovation instead of selecting for only one of the two strategies in pursuing superior performance. The paper tests the relationships between firm managerial capabilities, technological and marketing resources, innovation and internationalization strategies, and firm performance based on the assumptions of the resource-based view. The hypotheses are tested using the data from a survey on 169 Italian SMEs. The outcomes reveal that innovation and internationalization are complementary, and not alternative in the attainment of firm superior performance, both technological and marketing resources are positively associated with the business internationalization, whereas only technological resources contribute to the business innovativeness. Additionally, managerial capabilities are key for deploying the firm overall resource endowment.